Bijak Bermedia Sosial: Cegah Kenakalan Remaja Di Era Digital SMK Fajar Ciseeng, Jl. Fajar, RT.007/RW003, Kelurahan Babakan, Kecamatan. Ciseeng, Kabupaten Bogor, Jawa Barat 16120 - Dipa Saputra; Afisa Elsa Pangestu; Farel Aufriza Rayhan; Irfan Rizka Akbar (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The use of social media in the school environment often becomes an initial space for students to shape their self-identity, interact, and build social relationships in the digital era. In the context of SMK Fajar Ciseeng, the intensity of students’ social media use has its own dynamics, influenced by technological developments, digital trends, as well as the diverse characteristics and backgrounds of the students. This Community Service Activity (Pengabdian kepada Masyarakat/PKM) aims to examine and provide guidance on the importance of wise and responsible social media use as an effort to prevent juvenile delinquency. The program is implemented through observation, educational outreach, interactive discussions, and the presentation of case studies involving students, teachers, and the school community. Through this series of activities, students are expected to understand the positive and negative impacts of social media, recognize the boundaries of digital ethics, and increase awareness of responsibility in behaving within digital spaces. In addition, this activity encourages the creation of a healthy, safe, and ethical digital environment as part of a positive school social climate. Therefore, this PKM activity is expected to make a tangible contribution to improving students’ digital literacy and preventing juvenile delinquency at SMK Fajar Ciseeng.